(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The rapid advances in smartphones’ technology, reflected in terms of light weight, small size, and easy portability, has rendered an inevitable rapid increase in number of smartphone users and smartphone addicts among ordinary population. Faulty use of smartphones would eventually put an overdue mechanical demand and load on shoulder and scapular muscles, that precipitate minor traumas and consequently shoulder pain and diminished performance. Purposes To investigate the effect of postural correction exercises on shoulder muscle performance in subjects addicting smartphones. Subjects Forty subjects addicting smartphones of both genders were recruited and distributed at random to the control and experimental group. Subjects’ age in group (A) and (B) were (28.1±3.8) and (28.8±4) years respectively, their height was (170.1±8.9) and (170.2±8.3) cm respectively, whereas their weight was (73.6±9.5) and (71.3±10.7) kg respectively. Materials and Methods all recruited subjects in both control and experimental group received traditional modalities to relieve pain in the form of infrared radiation and TENS. The experimental group (Group B) including twenty subjects received postural correction exercises in addition to the traditional modalities of relieving pain. Results As compared to the control group, shoulder muscles’ performance in the experimental group showed significant improvement. The improvement shown involved improved work, torque and work fatigue at angular velocity of 120°/sec. for shoulder flexors, extensors, abductors and internal rotators. Conclusion Postural correction exercises have significant effect on improving shoulder muscle performance in subjects showing postural deviation owing to smartphones addiction.